Rietveld Quantitative Analysis of Cast Super Duplex Steel - Mannheim-Cassierer, R (2012)
To interpret highly superimposed diffraction patterns, the Rietveld method together with conventional X-ray powder diffraction techniques were carried out on a series of heat-treated weldments of cast super duplex stainless steel. High temperature processing of this type of alloys causes embrittlement and loss of corrosion resistance owing to precipitation of intermediate phases, principally sigma-phase. The annealing processing of the samples proceeded at temperatures in the range of 800-950 °C for periods of time from 1 to 96Â h. This procedure permitted an accurate quantification of the microstructural components such as austenite, ferrite and sigma-phase in all studied samples. The contents of sigma-phase in the heat-affected zones of all weldments reached asymptotical values of 30-38 wt% after 96Â h of heat treatment.© 2012 JCPDS-ICDD.